Gambaran Mengkonsumsi Buah Stroberi Dalam Menghambat Pembentukan Plak Di Pondok Putri 1 Kompleks Hartaco Jaya Kota Makassar - AR, Aisyah; Magfirah, Febi; Nasri, Eva Winda (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Maintaining a person's dental and oral health can avoid caries and periodontal disease. Plaque is a layer formed from food residue that sticks to the teeth that reacts with saliva, bacteria, enzymes, and sticky acids containing bacteria that form on the surface of the teeth and plaque occurs when eating foods containing carbohydrates, soft drinks, cakes or candy and remaining on the teeth. Chewing strawberries has many advantages, including, first mechanically, when chewing strawberries there is friction between the tooth surface and the fibers contained in strawberries so that it can remove plaque on the tooth surface. Objective To determine the effectiveness of consuming strawberries in inhibiting plaque formation in boarding house children at Pondok Putri 1, Hartaco Jaya Complex. Research Method This study used quantitative research, with a sample of 14 people using humans in the affordable population as samples, namely the before and after groups. The results of the study from the research data can be seen that consuming fruit after every meal, the plaque score formed was 0.58, while the plaque score for those who did not consume strawberries was 0.62. Based on table 3, the average plaque index before consuming strawberries was 3.08 and the average plaque index after consuming strawberries was 0.58. The difference between the average plaque index before and after consuming strawberries was 2.37. The results showed that the plaque index decreased after consuming strawberries. While those who did not consume strawberries had an average plaque index before of 1.50 and an average plaque index after of 0.62. The difference between the average plaque index before and after.